Los nahuas de Tzintzuntzan-Huitzitzilan, Michoacán: historia, mito y legitimación de un señorío prehispánico - Hans Roskamp (Journal de la Société des Américanistes)
The Nahuas of Tzintzuntzan-Huitzitzilan, Michoacán: history, myth and legitimization of a Prehispanic señorío. Modern historiography on 15th and early 16th century Michoacán emphasizes the political-economical success of the Tarascans and their uacúsecha lineage but pays relatively little attention to other ethnic groups that lived in the region. This article deals with the nature and strength of the historical traditions of the Nahuas in Michoacán, paying special attention to the case of Tzintzuntzan-Huitzitzilan, a place which at the time of the Spanish conquest was the capital of the uacúsecha señorío. The presence of the Nahuas and their interaction with the Tarascans not only became part of the diverse local visions of the past but possibly also influenced the historical views of the Nahua neighbors from West and Central México. The latter frequently established a direct relation with the population of Michoacán in narratives about origin, migration and foundation of their own señoríos. These historical traditions clearly served the purpose of legitimization and constitute a complex blend of registered events, cosmological representations, as well as religious and political symbolism.